Use of a latency‐based demand assessment to identify potential demands for functional analyses. Issue 4 (29th July 2016) - Call, Nathan A.; Miller, Sarah J.; Mintz, Joslyn Cynkus; Mevers, Joanna Lomas; Scheithauer, Mindy C.; Eshelman, Julie E.; Beavers, Gracie A.
Abstract : Unlike potential tangible positive reinforcers, which are typically identified for inclusion in functional analyses empirically using preference assessments, demands are most often selected arbitrarily or based on caregiver report. The present study evaluated the use of a demand assessment with 12 participants who exhibited escape‐maintained problem behavior. Participants were exposed to 10 demands, with aversiveness measured by average latency to the first instance of problem behavior. In subsequent functional analyses, results of a demand condition that included the demand with the shortest latency to problem behavior resulted in identification of an escape function for 11 of the participants. In contrast, a demand condition that included the demand with the longest latency resulted in identification of an escape function for only 5 participants. The implication of these findings is that for the remaining 7 participants, selection of the demand for the functional analysis without using the results of the demand assessment could have produced a false‐negative finding.